2017
DOI: 10.1186/s12864-016-3380-0
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for stomatal and photosynthetic traits related to salinity tolerance in barley

Abstract: BackgroundStomata regulate photosynthesis and transpiration, and these processes are critical for plant responses to abiotic stresses such as salinity. A barley double haploid population with 108 lines derived from a cross between CM72 (salt-tolerant) and Gairdner (salt-sensitive) was used to detect quantitative trait loci (QTLs) associated with stomatal and photosynthetic traits related to salinity tolerance.ResultsA total of 11 significant QTLs (LOD > 3.0) and 11 tentative QTLs (2.5 < LOD < 3.0) were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…Low transcript levels do not necessarily predict low protein levels since it has been shown that there is only a weak correlation between transcript and protein levels in cells (Kosti et al, 2016; Perl et al, 2017). Consistent with this finding, recent studies using single cell PCR analysis have shown that Pax7 transcript levels are below the limit of detection in approximately 10% of the satellite cells (Cosgrove et al, 2014; Quarta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Low transcript levels do not necessarily predict low protein levels since it has been shown that there is only a weak correlation between transcript and protein levels in cells (Kosti et al, 2016; Perl et al, 2017). Consistent with this finding, recent studies using single cell PCR analysis have shown that Pax7 transcript levels are below the limit of detection in approximately 10% of the satellite cells (Cosgrove et al, 2014; Quarta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As was previously discussed, g s , canopy structure, and functional stay-green are among the most addressed traits studied to improve plant photosynthesis in crops. The relationship between QTLs and gs has been established in rice [160][161][162], wheat [163][164][165][166], barley [167,168], and sorghum [169], although a more in-depth mapping is required to enable the identification of genes directly related to the anatomy and functioning of the stomata. Changes in leaf angle and plant architecture are features of interest in cereal breeding programs [170,171].…”
Section: Photosynthesis-based Breeding Under the Scenario Of Global Cmentioning
confidence: 99%
“…Liu et al (2017) related stomatal traits and yield to salinity tolerance, and found QTLs on chromosomes 1H (11 cM) and 3H (58.9 cM) associated with grain yield, and QTLs on chromosome 1H (121.4 cM) and 2H (10.3 cM) associated with stomatal pore area and stomatal conductance, respectively. Moreover, QTLs associated with salinity tolerance were identified at different developmental stages such as salinity tolerance at germination (Mano and Takeda 1997), seedling (Ellis et al 2002;Mano and Takeda 1997), and reproductive stage (Liu et al 2017;Xue et al 2009). Barati et al (2017) identified several QTLs contributing to agronomic performance in the field under nonsaline and saline conditions using a doubled-haploid population derived from Clipper and Sahara.…”
Section: Soil Salinitymentioning
confidence: 99%